Effect of hydraulic retention time on continuous electricity production from xylose in up-flow microbial fuel cell. (9th November 2017) - Haavisto, Johanna M.; Kokko, Marika E.; Lay, Chyi-How; Puhakka, Jaakko A.
Abstract: Aerobic wastewater management is energy intensive and thus anaerobic processes are of interest. In this study, a microbial fuel cell was used to produce electricity from xylose which is an important constituent of lignocellulosic waste. Hydraulic retention time (HRT) was optimized for the maximum power density by gradually decreasing the HRT from 3.5 d to 0.17 d. The highest power density (430 mW/m 2 ) was obtained at 1 d HRT. Coulombic efficiency decreased from 30% to 0.6% with HRTs of 3.5 d and 0.17 d, respectively. Microbial community analysis revealed that anode biofilm contained known exoelectrogens, including Geobacter sp. and fermentative organisms were present in both anolyte and the anode biofilm. The peak power densities were obtained at 1–1.7 d HRTs and xylose degraded almost completely even with the lowest HRT of 0.17 d, which demonstrates the efficiency of up-flow MFC for treating synthetic wastewater containing xylose. Highlights: A two-chamber up-flow MFC was continuously fed with xylose. Hydraulic retention times between 0.17 and 3.5 d were tested. Highest power density of 430 mW/m 2 was found with 1 d HRT. Xylose degradation was above 96% with all HRTs.